Reduction of Structural Defects in the GaSb Buffer Layer on (001) GaP/Si for High Performance InGaSb/GaSb Quantum Well Light-Emitting Diodes - Yeon, Eungbeom; Woo, Seungwan; Chu, Rafael Jumar Abella; In-Hwan Lee; Ho Won Jang; Jung, Dae hwan; Choi, Won Jun (American Chemical Society, 2023)
Monolithic integration of GaSb-based optoelectronic devices on Si is a promising approach for achieving a low-cost, compact, and scalable infrared photonics platform. While tremendous efforts have been put into reducing dislocation densities by using various defect filter layers, exploring other types of extended crystal defects that can exist on GaSb/Si buffers has largely been neglected. Here, we show that GaSb growth on Si generates a high density of micro-twin (MT) defects as well as threading dislocations (TDs) to accommodate the extremely large misfit between GaSb and Si. We found that a 250 nm AlSb single insertion layer is more effective than AlSb/GaSb strained superlattices in reducing both types of defects, resulting in a 4× and 13× reduction in TD density and MT density, respectively, compared with a reference sample with no defect filter layer. InGaSb quantum well light-emitting diodes were grown on the GaSb/Si templates, and the effect of TD density and MT density on their performance was studied. This work shows the importance of using appropriate defect filter layers for high performance GaSb-based optoelectronic devices on standard on-axis (001) Si via direct epitaxial growth.